2008
DOI: 10.1017/s0033291708002754
|View full text |Cite
|
Sign up to set email alerts
|

Suicide after bereavement: an overlooked problem

Abstract: Background. To examine the effect of time on suicide after bereavement among widowed persons.Method. The data were extracted from Swiss mortality statistics for the period [1987][1988][1989][1990][1991][1992][1993][1994][1995][1996][1997][1998][1999][2000][2001][2002][2003][2004][2005]. The time between bereavement and subsequent death, specifically by suicide, was determined by linkage of individual records of married persons. The suicide rates and the standardized mortality ratios in the first week/month/yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 14 publications
(17 reference statements)
4
43
0
1
Order By: Relevance
“…In the week following widowhood, a study from Finland reported a relative risk for ischemic heart disease of 2.3 for men and 3.5 for women (Kaprio et al, 1987), and suicide rates in Switzerland have also been reported to be highest in this period (Ajdacic-Gross et al, 2008). These findings correspond well with ours.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the week following widowhood, a study from Finland reported a relative risk for ischemic heart disease of 2.3 for men and 3.5 for women (Kaprio et al, 1987), and suicide rates in Switzerland have also been reported to be highest in this period (Ajdacic-Gross et al, 2008). These findings correspond well with ours.…”
Section: Discussionsupporting
confidence: 90%
“…In the United States, extremely high suicide rates were observed among widowed men under 50 years of age (Luoma and Pearson, 2002); in Denmark, the majority of older persons who commit suicide are widowed (Erlangsen et al, 2004); and in Switzerland, suicide risk was shown to be increased in widowed individuals (Ajdacic-Gross et al, 2008). However, the small number of deaths due to causes like suicide create a challenge when trying to pinpoint the excess risk a few days after widowhood.…”
Section: Introductionmentioning
confidence: 99%
“…This is significant given that those bereaved by suicide are at a substantially higher risk of suicide themselves (Ajdacic-Gross et al, 2008;Department of Health, 2010;Krysinska, 2003). Therefore strategies to support and understand those affected are integral to suicide prevention.…”
Section: Discussionmentioning
confidence: 99%
“…We repeated analyses weighing factors associated with study participation to verify the robustness of our results after correction for selection bias [49]. Then we compared traditional service use between participants who used online information versus those who did not with bivariate chi-square tests.…”
Section: Methodsmentioning
confidence: 99%